Study on adsorption of phosphate from aqueous solution by nanomaterial CeO2 - Duc, Dao Hong; Nhiem, Dao Ngoc; Bac, Nguyen Quang; Trung, Do Quang (Vietnam Journal of Chemistry, 2017)
The synthesis of nanosize single phase CeO2 by gelatine gel combustion method was investigated. The prepared material was characterized by X- ray diffraction, thermogravimetric and differential thermal analysis, scanning electron microscopy and transmission electron microscopy measurements. At optimum conditions, such as pH 3, the molar ratio of Ce4+/gelatine 1/1, and a calcination temperature of 550 oC for 2 hours, the material with average size < 30 nm was synthesized. From the results of phosphate adsorption, adsorption equilibrium time of the material was determined at 60 minutes. The phosphate adsorption process in aqueous solution followed the Langmuir isothermal model with Qmax= 152.66 mg/g. Keywords. CeO2, gelatine, combustion method, phosphate (PO43-) adsorption.